Construções de representações sociais entre homens em anúncios pessoais eletrônicos - Costa, Vitor Hugo Chaves (2010)
This research investigates how homoerotic males represent themselves in personal ads from internet. Thus, the theoretical background was Appraisal Theory, Martin & White (2005), discoursive studies from Bakhtin s Circle, Cultural Gender Studies and Social Representation Theory, Moscovici (1981). Appraisal Theory explains the evaluative aspect of language, three semantic fields (affect, appreciation and judgement). According to Bakhtin s Circle Studies, language is a social phenomena. Cultural Gender Studies there is Male Domination and Heterosexism in our social cultural context. Social representations are entities of mental, social, cultural and historical order, constructed collectively, making possible to social groups to perceive, to understand and to act on the world (MOSCOVICI, 2003). It was analyzed 308 personal ads from the following sites: Almas Gêmeas (10), Super Encontros (25), Manhunt (122), GLS Planet (81) e Viva Street (70). The analysis was based on three dimensional model to discourse from Fairclough (2001), which comprises of social practice, discursive practice and text. In text analysis, it was explored the semantic fields of Appraisal Theory (affect, judgement and appreciation), which was used to define how the advertisers represented themselves. The main categories had been: affect (romantic, promiscuous, antieffeminate, interracials, intraracials, friends, cautious and adventurers), appreciation (bears, shaved, novices, experts, olds, fits, unfits, whites and afros) and judgment (effeminates, discretes, actives, passives, versatiles and serious).